NEW DATA ON THE PRECAMBRIAN AGE OF MARUNKEU ECLOGITES (POLAR URALS) - Andreichev V.L.; Ronkin Y.L.; Serov P.A.; Lepikhina O.P.; Litvinenko A.F. (My University, 2007)
The age of eclogites (Precambrian or Middle Paleozoic) constituting the Marunkeu Block remains one of the key geological problems of the Polar Urals. It is crucial for dating subduction responsible for crystallization of eclogites. The Marunkeu Block is located on the eastern limb of the northern Polar Urals segment of the central Uralian Uplift. The Marunkeu Block includes different (in lithology and genesis), highly metamorphosed rocks (eclogites associated with ultramafics, migmatites, and garnet amphibolites) that are confined to the axial zone of the block corresponding to the southeastern part of the synonymous ridge (Slyudyanaya Gorka area). The flanks are composed of gneisses, feldspar amphibolites, and amphibole and micaceous schists. In the northern part, amphibolites and glaucophane schists are dominant rocks, while eclogites are missing. Widespread are lithology-variable blastomilonites and migmatites with signs of multiphase granitization and metasomatism. The block has tectonic contacts with the Upper Riphean greenschist volcanosedimentary Nyarovei Group.
Keywords: Precambrian; Precambrian::Proterozoic::Mesoproterozoic; Докембрий::Протерозой::Мезопротерозойская